Anesthetic efficacy of a combination of hyaluronidase and lidocaine with epinephrine in inferior alveolar nerve blocks. - Ridenour, S. (2001)
The purpose of this prospective, randomized, double-blind study was to determine the anesthetic efficacy of a buffered lidocaine with epinephrine solution compared to a combination buffered lidocaine with epinephrine plus hyaluronidase solution in inferior alveolar nerve blocks. Thirty subjects randomly received an inferior alveolar nerve block using 1 of the 2 solutions at 2 separate appointments using a repeated-measures design. Mandibular anterior and posterior teeth were blindly pulp tested at 4-minute cycles for 60 minutes postinjection. No response from the subject to the maximum output (80 reading) of the pulp tester was used as the criterion for pulpal anesthesia. Anesthesia was considered successful when 2 consecutive readings of 80 were obtained. A postoperative survey was used to measure pain and trismus. The results demonstrated 100% of the subjects had profound lip numbness with both solutions for inferior alveolar nerve blocks. The anesthetic success rates for individual teeth ranged from 20 to 80%. There were no significant differences (P > .05) between the 2 solutions. However, the combination lidocaine/hyaluronidase solution resulted in a significant increase in postoperative pain and trismus. It was concluded that adding hyaluronidase to a buffered lidocaine solution with epinephrine did not statistically increase the incidence of pulpal anesthesia in inferior alveolar nerve blocks and, because of its potential tissue damaging effect, it should not be added to local anesthetic solutions for inferior alveolar nerve blocks.